A two-stage design with two co-primary endpoints - James X. Song (Contemporary Clinical Trials Communications, 2015)
Two-stage designs are commonly used in phase II oncology trial to mitigate the risk of exposing patients to an inefficacious drug. Typically, the decision of moving into stage 2 enrollment is made based on response rate in stage 1 patients; and trials are designed in the hypothesis testing framework. When the primary objective of a trial involves more than one efficacy endpoints it is desirable to extend the two-stage design to a setting that accommodates two hypotheses while controlling overall type I and II errors (α and β). In this manuscript, we propose a simple method of searching stopping boundaries of both hypotheses simultaneously that satisfy α and β constrains using binomial distribution. Several design characteristics of these selected boundaries are further examined in order to choose the most desirable design based on an objective function. Simulation is used to confirm the results. A trial design in metastatic breast cancer where both response rate and health-related quality of life are of interest is used as an example of the application of the proposed method. In conclusion, the proposed design is an extension of Simon Two-Stage Design. It can be applied to phase II oncology trials with two independent co-primary efficacy endpoints.